The impact of biochar on the activities of soil nutrients acquisition enzymes is potentially controlled by the pyrolysis temperature: A meta-analysis - Liao, Xiaolin; Kang, Hojeong; Haidar, Ghulam; Wang, Weifeng; Malghani, Saadatullah (Geoderma, 2022)
•Biochar produced at < 500 ℃ pyrolysis temperature triggers soil enzymes.•Biochar produced ≥ 500 ℃ shows negligible impact on soil enzymes response.•Soil and biochar characteristics play secondary roles in the effects of biochar on soil enzymes activities. Understanding the responses of soil enzymes that catalyze the decomposition of organic matter is critical for understanding the mechanisms of biochar effects in agricultural soils. In this study, we conducted a global meta-analysis based on 1354-paired observations extracted from 125 published and 4 unpublished articles to explore the effects of biochar on the activities of soil nutrients-acquisition enzymatic groups. The meta-analysis revealed contrasting responses of soil enzymes to biochar amendment at the individual and group levels. Pyrolysis temperature was the dominant factor determining the effects of biochar on soil enzyme activities. Low-temperature biochar produced at < 500 ℃ enhanced the activities of almost all soil enzymatic groups involved in carbon (C), nitrogen (N), and phosphorus (P) acquisition extracellular soil enzymes, and dehydrogenase (DHA) with mean effect sizes of 4%, 23%, 12%, and 22%, respectively. A significant role of different parameters associated with low-temperature biochar, soil, and experimental conditions was evident on the activity of C-acquisition enzymes. In contrast, N and P-acquisition enzymes showed consistently positive responses to low-temperature biochar addition regardless of other parameters. High-temperature biochar produced ≥ 500 ℃ showed negligible effect on C-, N-, P- acquisition enzymes and DHA activity with mean effect sizes of 2%, 6%, 1%, and 0.5%, respectively. Soil pH, texture, C contents, and biochar application rates were the dominant factors influencing biochar effects on soil enzyme activities. The long-term field experiments usually showed different responses to biochar addition from lab incubation and short-term field experiments. Overall, the present meta-analysis provides comprehensive information elucidating the effects of low and high-temperature biochars on soil enzymes in agroecosystems to enhance C sequestration or soil fertility.